The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/plants10050924
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Biochemical Responses of Potato Cultivars under In Vitro Lithium Chloride and Mannitol Simulated Salinity and Drought Stress

Abstract: Globally, drought and salinity stress critically constrain potato (Solanum tuberosum L.) production. Considering the impact of these stresses on crops and increasing food demand, insight into both tolerance and susceptibility is essential. The present study screens two potato cultivars, BARI-401 and Spunta, for their tolerance to simulated salinity and drought by in vitro LiCl and mannitol exposure. Plantlets treated with a range of LiCl (0, 10, 30, and 40 mM) and mannitol (0, 50, 100, 200, and 250 mM) concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 63 publications
(82 reference statements)
0
8
0
3
Order By: Relevance
“…[ 91 ]. Depending on the tolerance and sensitivity of genotypes, differences in the expression level of antioxidant enzymes can be found [ 92 , 93 ]. In addition, phenolic compounds, being nucleophiles, can inhibit lipid peroxidation through their ability to remove free radicals and prevent damage caused by them [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 91 ]. Depending on the tolerance and sensitivity of genotypes, differences in the expression level of antioxidant enzymes can be found [ 92 , 93 ]. In addition, phenolic compounds, being nucleophiles, can inhibit lipid peroxidation through their ability to remove free radicals and prevent damage caused by them [ 94 ].…”
Section: Resultsmentioning
confidence: 99%
“…Multiple research studies found that salinity and drought stress had an additive effect on dry-matter accumulation; thus, the two stresses coupled had a more considerable negative impact [ 54 , 55 , 56 ]. According to certain studies, salinity causes an increase in the concentration of NaCl, which results in a decrease in shoot length [ 57 , 58 , 59 ]. However, differing levels of water stress did not significantly impact shoot length, SDW, and RDW [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Key Laboratory of Crop Genetic Improvement and Germplasm Innovation at Gansu Agricultural University provided tissue cultured seedlings of C16 and C119 ( Table 1 ). Stem sections of potato test-tube plantlets were transferred to paper boats floating on liquid MS (Murashige and Skoog) medium containing 0 mM (control) or 75 mM or 150 mM mannitol (drought stress treatments) ( Hamooh et al., 2021 ; Sattar et al., 2021 ). After 15, 20, and 25 days of growth, the paper boats containing the tube seedlings were carefully removed.…”
Section: Methodsmentioning
confidence: 99%